Amateur subtitling in a dubbing country: The reception of Iranian audience - Khoshsaligheh,Masood (2019)
Although dubbing is the official and dominant modality of translating foreign films and television series in Iran, amateur subtitling has been increasingly used by the Iranian audience for audiovisual products that are not dubbed, or at least not soon enough or not without substantial 'cultural appropriation.' Given the increasing attention paid to viewers' reception in the domain of audiovisual translation, this study attempts to explore the reception of Iranian viewers of the non-professional subtitling into Persian. Both qualitative and quantitative approaches were employed for the present research. Initially, the qualitative analysis of the focus groups conducted with consumers of such products suggested five main themes: translational, translatorial and technical expectations as well as the advantages and disadvantages. The quantitative analysis of the survey data confirmed the five themes in the second phase of the study.